2013
DOI: 10.1002/gbc.20038
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of Fe(III) and humic acid reduction to ecosystem respiration in drained thaw lake basins of the Arctic Coastal Plain

Abstract: Previous research showed that anaerobic respiration using iron (Fe) oxides as terminal electron acceptor contributed substantially to ecosystem respiration (ER) in a drained thaw lake basin (DTLB) on the Arctic coastal plain. As DTLBs age, the surface organic layer thickens, progressively burying the Fe‐rich mineral layers. We therefore hypothesized that Fe(III) availability and Fe reduction would decline with basin age. We studied four DTLBs across an age gradient, comparing seasonal changes in the oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 58 publications
3
69
0
Order By: Relevance
“…The most extensive work on Fe reduction in tundra soils has been done by Lipson and colleagues (5,33,34), who investigated anaerobic processes in Arctic permafrost soils near Barrow, AK. These studies showed that anaerobic respiration coupled to Fe oxide reduction is a primary terminal electron-accepting process, accounting for 40 to 60% of the ecosystem respiration (5,33,34). Detailed mineralogical analysis by these authors revealed an abundance of poorly crystalline readily reducible iron oxides in these moist soils.…”
Section: Discussionmentioning
confidence: 99%
“…The most extensive work on Fe reduction in tundra soils has been done by Lipson and colleagues (5,33,34), who investigated anaerobic processes in Arctic permafrost soils near Barrow, AK. These studies showed that anaerobic respiration coupled to Fe oxide reduction is a primary terminal electron-accepting process, accounting for 40 to 60% of the ecosystem respiration (5,33,34). Detailed mineralogical analysis by these authors revealed an abundance of poorly crystalline readily reducible iron oxides in these moist soils.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Fe(III) can serve as terminal electron acceptor for microbial respiration of organic matter. Lipson et al (2010Lipson et al ( , 2012Lipson et al ( , 2013 report that iron (Fe) reduction dominates anaerobic respiration in shallow peat soils located on the Arctic coastal plain near Barrow, Alaska. These saturated, organic-rich soils contain high concentrations of dissolved and colloidal Fe that undergo seasonal redox cycling due to microbial activity and fluctuations in the water table.…”
Section: Introductionmentioning
confidence: 99%
“…Redox status also varies along climate gradients at landscape and regional scale, where redox potential tends to decline under high rainfall conditions (Silver et al 1999, 2014, Schuur and Matson 2001. While the importance of soil redox has been investigated at small (i.e., soil aggregate) and larger (i.e., topographic and climate gradients) scales in soils, spatial variability in soil redox has not, except with rare exceptions (e.g., Lipson et al 2013), been investigated at the plot scale (centimeters to meters). It is at this scale that most biogeochemical processes are measured in the field.…”
Section: Introductionmentioning
confidence: 99%